Child Poverty Increasing - Suzanna Smith (EDIS)
“When we think of poor children, the images of starving children across the world may come to mind. However, the numbers of children living in poverty right here in the U.S. might surprise you…” This transcript of a two-minute Family Album Radio broadcast was published by the UF Department of Family, Youth and Community Sciences, March 2012.